A methodology to relate octane numbers of binary and ternary n-heptane, iso-octane and toluene mixtures with simulated ignition delay times. (15th November 2015) - Badra, Jihad A.; Bokhumseen, Nehal; Mulla, Najood; Sarathy, S. Mani; Farooq, Aamir; Kalghatgi, Gautam; Gaillard, Patrick
Highlights: Potential correlations between RON and MON and IDT for TPRF blends are investigated. Constant and variable volume ignition delay times are tested. The RON-like 850 K and 50 atm proposed conditions best correlated with the RON. The CR dependent volume profiles lead to better correlation with RON and MON. Abstract: Predicting octane numbers (ON) of gasoline surrogate mixtures is of significant importance to the optimization and development of internal combustion (IC) engines. Most ON predictive tools utilize blending rules wherein measured octane numbers are fitted using linear or non-linear mixture fractions on a volumetric or molar basis. In this work, the octane numbers of various binary and ternary n-heptane/iso-octane/toluene blends, referred to as toluene primary reference fuel (TPRF) mixtures, are correlated with a fundamental chemical kinetic parameter, specifically, homogeneous gas-phase fuel/air ignition delay time. Ignition delay times for stoichiometric fuel/air mixtures are calculated at various constant volume conditions (835 K and 20 atm, 825 K and 25 atm, 850 K and 50 atm (research octane number RON-like) and 980 K and 45 atm (motor octane number MON-like)), and for variable volume profiles calculated from cooperative fuel research (CFR) engine pressure and temperature simulations. Compression ratio (or ON) dependent variable volume profile ignition delay times are investigated as well. The constant volume RON-like ignition delay times correlation with RON was the best amongst the other studied conditions. The variable volume ignition delay times condition correlates better with MON than the ignition delay times at the other tested conditions. The best correlation is achieved when using compression ratio dependent variable volume profiles to calculate the ignition delay times. Most of the predicted research octane numbers (RON) have uncertainties that are lower than the repeatability and reproducibility limits of the measurements. Motor octane number (MON) correlation generally has larger uncertainties than that of RON.